In-Group Favoritism in the Gain and Loss Domain: Experimental Evidence from China and the US - Armenak Antinyan; Tigran Aydinyan; Anna Ressi; Lilia Wasserka-Zhurakhovska (CESifo GmbH, 2025)
How individuals allocate resources across social groups depends on economic conditions. While prior research has documented strong in-group favoritism in domains reflecting favorable economic conditions, it remains unclear how this tendency shifts in domains that reflect economic downturns. We investigate this question by running two artefactual field experiments, one in China and one in the US, where participants, depending on the treatment, either allocate money to in-group and out-group recipients (reflecting the gain domain) or take money away from them (reflecting the loss domain). In both experiments, we document in-group favoritism in the gain domain, which decreases in the loss domain. However, this reduction in in-group favoritism is not due to a greater tendency to treat different recipients equally. Instead, we find that the loss domain leads to more dispersed allocation decisions. This pattern translates into in-group favoritism being counteracted by a higher share of participants who favor out-group recipients.
Keywords: C99; D30; D63; D81; J10; J15; 330; in-group favoritism; group bias; discrimination; loss vs. gain domain; social preferences